Huge Candida albicans normal native tricuspid valve endocarditis - Massimiliano Guerriero; Francesco Colasurdo; Anna Maria Pollio (University of São Paulo, 2018)
Fungal endocarditis has become an important infection associated with medical progress and the modern lifestyle. In particular, Candida spp. is a rare but important cause of infective endocarditis. We report the case of a 28-year-old woman-quadriplegic and bedridden from birth-who died after repeated episodes of pneumonia treated with different regimens of intravenous antibiotics. A medico legal autopsy was performed, which diagnosed severe Candida native valve infective endocarditis (CIE). This case report illustrates the prolonged use of antibiotic treatment as a possible risk factor for the development of CIE. We also considered how the bedridden condition and the presence of a central venous catheter may be additional risk factors for the development of this entity. Finally, we examined the absence of peripheral embolization in the setting of endocarditis of the right side of the heart.